The Association Between Mothers' Knowledge of Comple-mentary Therapies and the Utilization of Infant Massage Among Toddlers at Kenanga Posyandu - Hanik Khairun Nisa; Susmita Susmita; Suci Sulistyorini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Infant massage is one of the complementary therapies widely used to support the growth, development, and overall well-being of toddlers. However, the utilization of infant massage among mothers is often influenced by their level of knowledge regarding complementary therapies. This study aimed to analyze the association between mothers’ knowledge of complementary therapies and the utilization of infant massage among toddlers at Kenanga Posyandu. A quantitative study with a cross-sectional design was conducted involving mothers who had toddlers registered at Kenanga Posyandu. Participants were selected using a purposive sampling technique. Data were collected through structured questionnaires assessing mothers’ knowledge of complementary therapies and their practice of infant massage. The data were analyzed using descriptive statistics and the Chi-square test to determine the relationship between the variables. The findings revealed that most mothers had a moderate to good level of knowledge regarding complementary therapies, and a majority reported utilizing infant massage for their toddlers. Statistical analysis showed a significant association between mothers’ knowledge and the utilization of infant massage (p < 0.05), indicating that mothers with higher knowledge levels were more likely to practice infant massage. These results suggest that knowledge plays an important role in encouraging the adoption of complementary health practices for toddlers. In conclusion, improving mothers’ knowledge through health education and community-based programs may increase the utilization of infant massage and contribute to better child health outcomes.